Tantangan Kepemimpinan Administrator Publik : Antara Politik dan Administrasi (Manajerial) - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Wima Y. Prasetyo (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
In each phase of development, political and administrative relations are always filled one room paradigmatic debate of public administration. One of the question, whether the public administration is more a political act or whether he should be an activity to practice the values and managerial considerations in the act. For some thinkers, the debate is no longer relevant and is considered finished with the map that at the level of executive leadership, public administration is the entity with political action. While on the lower level (bureaucracy), a professional managerial approach became the face of public administration leadership. This paper basically not appreciate the satisfaction of the mapping. For the writer, with a variety of environmental changes and trends of other administrative, managerial competence is essential for top level administrators and as important as managerial approach as practiced in midlle and lower levels of public administrators. On the other hand, although not intend to completely reject the political approach, this paper reveals that the style, action and leadership performance of public administrators who rely solely on political capacity will not be able to resolve detail the complexity of a problem with the right. Therefore, reform of government bureaucracy is necessary though, but he was not to be the best answer for the problems of public administration, but rather reform the government itself and more specifically the orientation of reform of public sector leadership